دور محاسبة التنمیة المستدامة فى زیادة موثوقیة التقاریر المالیة - دراسة میدانیة – - الجبلى ولید سمیر عبد العظیم (Finance and Business Economies Review, 2018)
The aim of this study is to know the role of sustainable development accounting in increasing the credibility of financial reports and the high level of confidence in them. The study reached a number of results, the most important of which is that the interest in measuring and disclosing the third elements of sustainable development accounting helps to increase the reliability of financial reports. Sustainable development in the form of sustainability reports, including quantitative and descriptive financial and non-financial information, while working to communicate them to stakeholders and stakeholders.